ASEAN Role and Regionalism in Southeast Asia - V.L. Sinta Herindrasti (Sociae Polites, 2010)
AbstractAs a regional-level organization that was founded in 1967 with 10 South East Asia state members (Indonesia, Malaysia, Philippines, Singapore, Thailand, Brunei, Vietnam, Laos, Myanmar, Cambodia), ASEAN is frequently seen as a unique case of regional integration manifested politically and economically. When society interconnection and integration are more globally intense and bring more serious attentions for social theorists through â€œGlobalizationâ€ concept, it cannot be denied that regionalism phenomenon is part of critical observation due to many unanswered questions: How does the regionalism process form? To what extend â€œglobalizationâ€ forms regionalism? How do state member actors face globalization process which is sometimes uncontrolled and unregulated with huge consequence such as 1997 Asia Financial Crisis? How is arrangement system of a regional community set up considering no one cannot ensure the final process of globalization in the future, etc.ASEAN â€“ proven not only an economic block â€“ possesses its own formula in effort to achieve its economic, politic and sociocultural goals and in theoretical understanding and praxis of globalization phenomenon are hoped to give significant contribution for ASEAN regional integration process while still being faithful to the main goal: to push development in various aspects through regional collaboration with every state member for social welfare.Keywords: regionalism, globalization, functional integration